Differences in Knowledge and Attitudes Before and After Oral and Dental Health Education in Elementary School Students at SDN 013 Palaran Samarinda City - Wiranti, Patih Atma; Listiyawati; Sawitri, Endang (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Dental and oral health problems are still widely found in children, especially at the age of 5-9 years. One of the factors that causes this problem is the lack of children's knowledge which has an impact on children's attitudes and actions towards their dental and oral health. One way that can be done as an effort to prevent dental and oral health problems at a child's age is by educating dental and oral health through flashcard game media. The purpose of this study is to find out the difference in knowledge and attitudes before and after dental and oral health education in students at SDN 013 Palaran, Samarinda City. Research Materials and Methods: This study was a pre-experimental research with a one group pre-test and post-test design. The research respondents came from students in grades 1, 2, and 3 at SDN 013 Palaran, Samarinda City with a sample size of 71 people who met the inclusion criteria. Data collection was carried out by knowledge and attitude questionnaires. The data from the study were analyzed using the Wilcoxon Signed Ranks Test. Results and Discussion: The results obtained were that most of the students' knowledge before education was in the medium category, which was 53.5%, and after education, the majority of students' knowledge was in the good category, which was 95.8%. The attitude of students before education is more in the medium category, namely 52.1%, and the attitude of students after education mostly shows a good category, which is 88.7%. The difference in knowledge and attitude before and after dental and oral health education showed p < 0.01 Conclusion: There are differences in knowledge and attitudes before and after dental and oral health education in students at SDN 013 Palaran, Samarinda City.